Foreign ownership structure, technology upgrading and exports: Evidence from Chinese firms - Sourafel Girma; Yundan Gong; Holger Görg; Sandra Lancheros (Kiel Institute for the World Economy (IfW), 2012)
We examine the role of foreign ownership structure in stimulating technology and skill upgrading, and exporting in Chinese manufacturing firms that were taken over by foreign owners. The analysis considers the period 2001 to 2007. We use a propensity score reweighted least squares estimation to control for the possible endogeneity of the acquisition decision. Our results indicate that there are strong effects on export activity post-acquisition for all types of ownership share. We also find that targets that are taken over with a less than 100 per cent foreign ownership share experience increases in new product development and R&D upgrading due to the acquisition. Overall, our results suggest that joint ventures between foreign owners and Chinese firms can contribute positively to China's 'science and technology take-off'.
Keywords: F23; 330; foreign acquisition; technology upgrading; exports; propensity score reweighting